"A stressful and frightening experience"? Children's nurses' perceived readiness to care for children with cancer following pre-registration nurse education: A qualitative study. (January 2017) - Jestico, Elizabeth; Finlay, Teresa
Abstract: Background: In the UK children with cancer are cared for by children's nurses in a variety of settings, specialist and non-specialist. Whilst post-registration specialist education is available to some nurses, many nurses rely solely on pre-registration education to competently care for these children. This study explores whether nurses perceive that this adequately prepares them. Objectives: To explore the extent to which qualified nurses perceive that pre-registration nurse education prepares them to care for children with cancer; to consider the implications for children's nursing pre-registration curricula. Design: A small-scale qualitative study was undertaken using an interpretivist approach. Methods: Semi-structured interviews were conducted with six qualified children's nurses in two clinical areas - a specialist children's cancer inpatient ward, and a general children's ward where inpatients included children with cancer. Results: Findings are discussed in relation to three emergent themes: Learning in Theory and Practice, Care of the Child and Family, and Resilience. Participants attached significance to the quantity and quality of practice experience. They reflected on barriers to specific and transferable theoretical learning and stressed the importance of integrating theory and practice. Understanding of family-centred care formed a significant part of their preparation. Preconceptions, communication with families and the emotional impact of this speciality were stressful. Improved pre-registration preparation may have developed participants' resilience. Conclusion: The complexities of caring for children with cancer and their families require well-prepared nurses. Participants' perceptions of preparedness were influenced by aspects of pre-registration education. Their experiences suggest that curricula should be practice-focused and include a range of placements. Specialist theoretical content must be integrated with practice and transferability of knowledge and skills made explicit. Reflection and problem-based learning may foster coping mechanisms and resilience that will equip them to care for children with cancer. Highlights: Perceptions of preparedness influenced by aspects of pre-registration education Integration of theory and practice crucial to prevent barriers to learning Understanding of family-centred care significantly supports preparation. Preconceptions, communication with families and emotional impact create stress Reflection and problem-based learning may foster coping mechanisms and resilience